2001
DOI: 10.1002/ijc.1199
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effect of a new selective matrix metalloproteinase inhibitor, MMI-166, on experimental pancreatic cancer

Abstract: The antitumor effect of a new matrix metalloproteinase inhibitor, MMI-166, which is a selective inhibitor of MMP-2 and -9, was examined in the hamster pancreatic cancer cell line PGHAM-1. In vitro, MMI-166 inhibited the gelatinase activity of MMP-2 and -9 derived from PGHAM-1 cells, and dose-dependently inhibited invasion of PGHAM-1 through a basement membrane-like barrier. MMI-166 showed no apparent cytotoxicity to PGHAM-1 cells in culture at 100 g/ml. MMI-166 (200 mg/kg) or vehicle were administered orally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 25 publications
(30 reference statements)
0
14
0
3
Order By: Relevance
“…Some studies have reported that lymph node metastasis in lung cancer closely correlated with the activation of MMP-2 and MT1-MMP, which are specific activators of MMP-2 on the cell surface (5,6). We speculated that MMI-166 with the inhibitory potential of MMP-2 activity contributes to the suppression of mediastinal lymph node metastasis in lung cancer, whereas previous reports show that MMI-166 inhibits tumor angiogenesis (22,23). The mechanism inhibiting lymph node metastasis in this study may include both the suppression of extracellular matrix degradation and the inhibition of angiogenesis at metastatic sites.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Some studies have reported that lymph node metastasis in lung cancer closely correlated with the activation of MMP-2 and MT1-MMP, which are specific activators of MMP-2 on the cell surface (5,6). We speculated that MMI-166 with the inhibitory potential of MMP-2 activity contributes to the suppression of mediastinal lymph node metastasis in lung cancer, whereas previous reports show that MMI-166 inhibits tumor angiogenesis (22,23). The mechanism inhibiting lymph node metastasis in this study may include both the suppression of extracellular matrix degradation and the inhibition of angiogenesis at metastatic sites.…”
Section: Discussionmentioning
confidence: 69%
“…There are several classes of agents which target the different steps involved in angiogenesis (21). These include (a) drugs inhibiting MMP, (b) drugs that block endothelial cell signaling by vascular endothelial growth factor and its receptor, (c) drugs that are similar to (22,23). This study also showed that the Ma44-3 lung cancer cell line moderately expressed both MMP-9 and MMP-2, and that 200 mg/kg body weight of MMI-166 significantly suppressed the Mediastinal metastatic lesions in the control group showed gelatinolytic activity on GN film, whereas mediastinal metastasis in the MMP-166 group showed no activity on GN film.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PGHAM-1 cell line (the hamster pancreatic cancer cell line) was derived from hamster pancreatic cancer cells induced with N-nitrosobis(2-oxopropyl)amine (12). Hamsters were anesthetized with Nembutal and then underwent laparotomy.…”
Section: Methodsmentioning
confidence: 99%
“…When PGHAM-1 derived from chemically induced hamster pancreatic cancer cells (11) is injected into the pancreas of hamsters, the cells develop ductal adenocarcinoma that closely resembles human pancreatic carcinoma and, like its human counterpart, frequently metastasizes to the liver. Thus, hamsters inoculated with PGHAM-1 cells represent an orthotopic pancreatic cancer model (12).…”
Section: Introductionmentioning
confidence: 99%